2019
DOI: 10.1016/j.ctro.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Fractional exhaled nitric oxide as a potential biomarker for radiation pneumonitis in patients with non-small cell lung cancer: A pilot study

Abstract: HighlightsWeekly FeNO during radiotherapy can be useful in predicting radiation pneumonitis.6 months of clinical follow-up is necessary to detect delayed radiation pneumonitis.Pulmonary function tests are not predictable for radiation pneumonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…So, it was necessary to detect both FeNO and blood NO levels in the same study to prevent the disturbance of therapy regimens. Another point that could not be overlooked was that there was great gap of follow up periods among different studies, from two days to more than two years [7,10,14,46,47,52]. Our results…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…So, it was necessary to detect both FeNO and blood NO levels in the same study to prevent the disturbance of therapy regimens. Another point that could not be overlooked was that there was great gap of follow up periods among different studies, from two days to more than two years [7,10,14,46,47,52]. Our results…”
Section: Discussionmentioning
confidence: 54%
“…During the past several decades, many researchers carried out a series of studies try to clarify the relationship between NO and lung cancer. These studies were mainly about comparisons of the levels of FeNO and blood NO between lung cancer patients and healthy controls , among lung cancer patients with different stages [7-9, 14, 17-21, 23, 27, 29, 31, 34, 36-39, 42] or types [6, 8, 9, 18-21, 24, 26, 27, 29, 31, 37-39, 42], and variations of these indexes from pretreatment to posttreatment [7,10,14,19,21,29,32,34,36,38,39,43,[46][47][48][49][50][51][52][53][54][55]. However, the results were not consistent among different studies, which might be due to ethnicity, age, pathological type, cancer stage, treatment regimen and follow up period.…”
Section: Introductionmentioning
confidence: 99%
“…So, it was necessary to detect both FeNO and blood NO levels in the same study to prevent the disturbance of therapy regimens. Another point that could not be overlooked was that there was great gap of follow up periods among different studies, from 2 days to more than 2 years [ 7 , 10 , 14 , 46 , 47 , 52 ]. Our results showed that FeNO level increased in long-term follow up subgroup but not in short-term follow up subgroup, while follow up period seemed not affect the pooled results of blood NO.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of RILI range from mild pulmonary symptoms to severe radiation pneumonitis (RP) [1]. Clinical RP of all grades is seen in 8-57% of cases, usually occurring 4-12 weeks after RT, and typically requires steroid treatment for several weeks [1,2,6,7]. Severe RP is observed in 6-8% of cases [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is insufficient information to enable the prediction of RP development and no radiological scales that assess the risk of RP based on grading of RILI are available [1,2,6,7,[13][14][15]. There are several tools to grade lung toxicity based on clinical and radiological data, such as the Radiation Therapy Oncology Group / European Organization for Research and Treatment of Cancer (RTOG/EORTC) [16], the Common Terminology Criteria for Adverse Events (CTCAE) [17], or the Southwest Oncology Group (SWOG) scoring system [18].…”
Section: Introductionmentioning
confidence: 99%